Multi-label classification based on sum-product networks - Llerena, Julissa Giuliana Villanueva (2017)
Multi-label classification consists of learning a function that is capable of mapping an object to a set of relevant labels. It has applications such as the association of genes with biological functions, semantic classification of scenes and text categorization. Traditional classification (i.e., single-label) is therefore a particular case of multi-label classification in which each object is associated with exactly one label. A successful approach to constructing classifiers is to obtain a probabilistic model of the relation between object attributes and labels. This model can then be used to classify objects, finding the most likely prediction by computing the marginal probability or the most probable explanation (MPE) of the labels given the attributes. Depending on the probabilistic models family chosen, such inferences may be intractable when the number of labels is large. Sum-Product Networks (SPN) are deep probabilistic models, that allow tractable marginal inference. Nevertheless, as with many other probabilistic models, performing MPE inference is NP- hard. Although, SPNs have already been used successfully for traditional classification tasks (i.e. single-label), there is no in-depth investigation on the use of SPNs for Multi-Label classification. In this work we investigate the use of SPNs for Multi-Label classification. We compare several algorithms for learning SPNs combined with different proposed approaches for classification. We show that SPN-based multi-label classifiers are competitive against state-of-the-art classifiers, such as Random k-Labelsets with Support Vector Machine and MPE inference on CutNets, in a collection of benchmark datasets.